Digital Transformation of PT Pos: Customer Loyalty In The Era of Security and Data Technology - Elfina O.P Damanik; Wico Jontarudi Tarigan; Jusra Tampubolon; Demak Claudia Yosephine Simanjuntak; Sabar Dumayanti Sihombing; Doris Yolanda Saragih; Poltak Pardamean Simarmata; Hengki Mangiring Parulian Simarmata (Jurnal Ekuilnomi, 2025)
Digital transformation can increase competitiveness and customer loyalty and become a business strategy, especially in the context of data security and trust. This study aims to empirically analyze the impact of digital transformation on customer loyalty, emphasizing the mediating role of customer trust at PT Pos Indonesia Pematangsiantar branch. Quantitative research using explanatory surveys of 100 customers selected by purposive sampling technique. The data collection instrument, with the distribution of questionnaires with a Likert scale of 5, has been tested for validity and reliability. Partial Least Squares-Structural Modeling based on SmartPLS 3. The results showed that digital transformation had a significant impact on customer loyalty trust (β = 0.836; p < 0.001) and loyalty (β = 0.906; p < 0.001). However, trust did not significantly impact loyalty (β = 0.076; p < 0.181). The study found that digital transformation can foster loyalty by providing a personalized, secure, and transparent service experience. This study's theoretical and practical implications are the strengthening of trust-based digital strategies for the postal services sector in developing countries